Mountain torques and synoptic systems in the Mediterranean - Egger, Joseph; Hoinka, Klaus-Peter (Quarterly Journal of the Royal Meteorological Society, 2008)
The mountains surrounding the Mediterranean exert torques T during the passage of North Atlantic systems which affect the angular momentum of the airflow passing over and around the massifs. The Alps, the Atlas range and the orographic block of Asia Minor are selected to investigate the typical flow conditions during torque events. These mountain ranges are small enough to justify a local angular momentum analysis. Both the zonal and the meridional components of a mountain’s torque (Tλ and Tϕ) are used as stratification parameters in a statistical investigation of the interaction of large-scale perturbations with this mountain. How are these flows affected by the obstacle? A simple scheme is tested which attempts to interpret results. The torque analysis singles out eastward-moving large-scale systems. Their isobars are oriented from southwest (northwest) to northeast (southeast) near the mountain in zonal torque Tλ (Tϕ) cases. The massifs tend to generate a low-level distortion of the pressure field such that the angular momentum of the flow over the mountain is reduced. These results can be explained within the framework of the scheme. The influence of the mountains on the pressure field is seen only at heights ≤4000 m. The low-level distortions of the pressure field contribute positively to the total torque for lags τ ≤ 0 in the Alps and for all lags −2 ≤ τ ≤ 2 days in Asia Minor, where only Tλ is evaluated. The impact of the Atlas mountains is seen only at τ = 0.